PENGUKURAN EFISIENSI PERBANKAN SYARIAH BERBASIS MANAJEMEN RISIKO - Ferry Prasetyia; Kanda Diendtara (Jurnal Keuangan dan Perbankan, 2011)
Efficiency was very important to note because it reflected the performance of a bank. This research aimed todetermine the level of efficiency of Islamic banking in Indonesia using risk management approach during theperiod 2005 to 2009. The samples in this research were commercial Islamic banks and sharia business unit.Commercial Islamic banks consisted of Bank Syariah Mandiri, Bank Syariah Mega, and Bank Muamalat.While the Sharia Business Unit consisted of Bank Permata and Bank Niaga. This research used Data EnvelopmentAnalysis (DEA) to obtain the level of efficiency of each bank which was being investigated. Inputvariables used in this study were the input variable of risk such as operational risk, liquidity risk, andfinancing risk. While the output used was the total financing, and revenue sharing. The results showed thatlevels of efficiency in this research period, Bank Syariah Mandiri and Bank Muamalat always had an efficientcondition. This was because the number of customers of the two banks were large and both of them had arelatively large branch network.